Rhes Counteracts Dopamine Neuron Degeneration and Neuroinflammation Depending on Gender and Age - Costa, Giulia; Pinna, Annalisa; Porceddu, Pier Francesca; Casu, Maria Antonietta; Di Maio, Anna; Napolitano, Francesco; Usiello, Alessandro; Morelli, Micaela (Frontiers in Aging Neuroscience, 2018)
We have recently shown that male Rhes knockout (KO) mice develop a mild form of spontaneous Parkinson’s disease (PD)-like phenotype, characterized by motor impairment and a decrease in nigrostriatal dopamine (DA) neurons. Experimental evidence has implicated neuroinflammation in PD progression, and the presence of activated glial cells has been correlated with DA neuron degeneration. Despite this, several factors, such as gender, have been found to affect DAergic neuron degeneration and influence neuroinflammation, explaining the differences between men and women in the aetiology of PD. On these bases, we studied age and gender differences in DA neuron degeneration and gliosis in the nigrostriatal system of adult (3-month-old) and middle aged (12-month-old) male and female Rhes wild-type (WT) and KO mice. Through immunohistochemistry, tyrosine hydroxylase (TH), microglial (complement type 3 receptor [CD11b]), and astroglial (glial fibrillary acid protein [GFAP]) increase, were evaluated. Adult male Rhes KO mice showed a decrease in TH and an increase in CD11b, both in the caudate putamen (CPu) and substantia nigra pars compacta (SNc), and an increase in GFAP in the CPu. In contrast, adult female Rhes KO mice showed only a decrease in TH in the SNc, whereas no modifications to the levels of GFAP and CD11b were observed in the CPu or SNc. Middle aged male Rhes KO mice showed a decrease in TH in the CPu and SNc, and an increase in GFAP and CD11b in the SNc. Middle aged female Rhes KO mice showed a decrease in TH in the CPu and SNc and an increase in CD11b only in the CPu, but no modifications to GFAP levels. The more marked DA neuron degeneration and neuroinflammation in male compared with female Rhes KO mice, while confirming the role of Rhes as an important protein for DA neuron survival, gives support to Rhes KO mice as a valuable preclinical model for studying the vulnerability factors of DA neuron degeneration as in PD.